1996
DOI: 10.1212/wnl.47.1.183
|View full text |Cite
|
Sign up to set email alerts
|

Language comprehension profiles in Alzheimer's disease, multi-infarct dementia, and frontotemporal degeneration

Abstract: We assessed language functioning in 116 age-, education-, and severity-matched patients with the clinical diagnosis of Alzheimer's disease (AD), multi-infarct dementia (MID) due to small-vessel ischemic disease, or a frontotemporal form of degeneration (FD). Assessments of comprehension revealed that patients with AD are significantly impaired in their judgments of single word and picture meaning, whereas patients with FD had sentence comprehension difficulty due to impaired processing of grammatical phrase st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 20 publications
5
75
0
1
Order By: Relevance
“…Consistent with previous findings, accuracy was lower for comprehension of nonbasic (type 2 and 3) than basic sentences in our group of patients (Grossman et al, 1996;Gorno-Tempini et al, 2004;Grossman and Moore, 2005) However, there was no significant difference in accuracy between types 2 and 3, showing that the anatomical differences we observed cannot simply be explained by differences in "general difficulty." Although sentences with embedded relative clauses are consistently considered "complex" structures, the classification of passive structures is less clear.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous findings, accuracy was lower for comprehension of nonbasic (type 2 and 3) than basic sentences in our group of patients (Grossman et al, 1996;Gorno-Tempini et al, 2004;Grossman and Moore, 2005) However, there was no significant difference in accuracy between types 2 and 3, showing that the anatomical differences we observed cannot simply be explained by differences in "general difficulty." Although sentences with embedded relative clauses are consistently considered "complex" structures, the classification of passive structures is less clear.…”
Section: Discussionsupporting
confidence: 92%
“…AD is a progressive neurodegenerative disease that selectively involves specific brain regions early in the course of the disease, including the hippocampus, posterolateral temporal-parietal cortex, and dorsolateral prefrontal cortex. This distribution of disease results in difficulty in retrieving information from familiar categories ("semantic memory") in 30% to 50% of AD patients (Grossman et al, 1996). Several imaging studies with AD patients have shown correlations between difficulty in semantic-mmory retrieval and functional cortical defects in dorsolateral prefrontal and posterolateral temporal-parietal cortices (Grossman et al, 1997;Desgranges et al, 1998).…”
Section: Using Novel Categories: Patient Studiesmentioning
confidence: 99%
“…Semantic knowledge was assessed by asking patients to judge the semantic category membership of 48 individually presented stimuli in response to a simple probe ("Is it an X?"). 25,26 One target category was tools and the other target category was vegetables. Stimuli were presented in a manner blocked by category and material.…”
mentioning
confidence: 99%